Desesperanza en pacientes adultos infectados con vih atendidos de manera ambulatoria - López Gonzales, Josselyn Eliza (2016)
Researches has shown that receive positive for HIV is associated with high levels of emotional stress and increase feelings of hopelessness. Hopelessness is conceived as a system of cognitive schemes that have in common negative expectations about the future. The aim of this study was to describe the levels of hopelessness in HIV-infected adult patients. Methods: Beck Hopelessness Scale was applied to 280 randomly selected patients infected with HIV treated as outpatients at the Clinic Unit Tropical and Infectious Diseases of the Regional Hospital of Trujillo. The results were interpreted according to the levels of the scale and was interpreted as follows: ≤3 minimal, and >3 significant. Results: Of the sample, 43.6% (n = 122) had minimum level of hopelessness, 40.4% (n = 113) mild, 14.3% (n = 40) moderate and 1.8% (n = 5) high. The 90% of the total (n = 252) receiving antiretroviral therapy and 10% (n = 28) do not receive. Of the first group, 42.9% (n = 108) had minimum level of hopelessness, 40.9% (n = 103) mild, 14.3% (n = 36) moderate and 2% (n = 5) high. Of the second group, 50% (n = 14) had minimum level of hopelessness, 35.7% (n = 10) mild and 14.3% (n = 4) moderate. Conclusion: The 56.4% of the sample had significant levels of hopelessness. The 57.1% of patients that receiving antiretroviral treatment had significant levels of hopelessness. The 50% of patients that not receiving antiretroviral treatment had significant levels of hopelessness